DISAPPEARING HERITAGE: PROMOTION AND PRESERVATION OF INDIAN FOLK ART - Choudhry, Zainab; Naseem, Bushra (International Journal of Research -GRANTHAALAYAH, 2025)
India is a country with rich customs and a varied population, all of which are deeply ingrained in the country's history. The folk arts, which are ancient manifestations of creativity and individuality passed down through the years, are the foundation of this cultural fabric. However, many of these old art forms are in danger of disappearing due to the quick speed of modernisation. This study examines the declining Indian folk arts and the need of preserving these priceless cultural assets. India's disappearing folk arts are live testaments to the many cultural landscapes that make up the nation, not only artistic expressions. From the intricate wood carvings of Kashmir to the vibrant Pattachitra paintings of Bengal and Odisha, each art form carries with it, centuries of history, tradition, and storytelling. However, many of these artistic expressions are in danger of disappearing completely as traditional lifestyles become increasingly urbanised and obsolete.